Direct Learning Model to Improve Aeronautical Knowledge of Cadets in Vocational Education School - Hariri, Ahmad; Hariadi, Eko; Wardhono, Arie (International Journal for Educational and Vocational Studies, 2020)
Method is a comprehensive plan to provide language learning materials on a regular basis, with no contradictory part, and all are based on a particular approach. The purpose of this study is to improve the Aeronautical Knowledge of Vocational Education Cadets in the Official Aviation School. The object chosen in this study is the Vocational Education Cadets of Official Aviation School. Based on the results of this study, it is proven that the direct learning model is able to increase Aeronautical Knowledge, which is indicated by the improvement of cadets’ achievement.